IMPLEMENTASI PENYELESAIAN SENGKETA TANAH ADAT DI MATARAM (STUDI PUTUSAN NOMOR : 2884 K/Pdt/2022) - Jovina; Roswita Sitompul; Kartina Pakpahan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
Land is seen as something very valuable and must be maintained by indigenous peoples. This can be seen in the life of the Indonesian people in each area of ​​residence and apart from the Indonesian people, land also has an impact on the government, in which case the government has the authority to control the land in use and allotment to the community. The research method used is in the form of normative juridical which is viewed from the UUPA, government regulations related to the same matter as well as literature studies and the type of data used is the Mataram District Court Decision Number 36/Pdt.G/2021/PN.Mtr, Mataram High Court Decision Number 231/PDT/2021/PT.MTR, and Court Decision Number 2884K/Pdt/2022 and reviewed based on customary law in Mataram. The results of this study are in the Cassation Decision Number 2884 K.Pdt/2022, it has been proven that PT Pertamina is the owner of the customary disputed land which was originally claimed to belong to the Plaintiff, namely the families of Ida WJ Gedok and Ida Nyoman Oka, but because the evidence they have is Proof of Garuda Pipil or Temporary Registration Certificate that is not re-registered so that it cannot be used as legal evidence because it is no longer valid.